ANALYTICAL VALIDATION OF CLOPIDOGREL IN HUMAN PLASMA THROUGH ULTRAHIGHPERFORMANCE LIQUID CHROMATOGRAPHY-TANDEM MASS SPECTROMETRY - Harahap, Yahdiana; Maysyarah, Innet (International Journal of Applied Pharmaceutics, 2017)
Objective: This study developed a sensitive, selective, and valid method for analyzing clopidogrel in human plasma using liquid chromatographytandem mass spectrometry (LC-MS/MS). Methods: The chromatography separation was performed on the waters ACQUITY UPLC Class BEH C18 1.7 Î¼m (2.1 Ã— 100 mm) column, consisting of 0.1% formic acid in water and 0.1% formic acid in acetonitrile (30-70) as the mobile phase, and an isocratic elution with a flow rate of 0.2 mL/minutes. The mass detection was performed using a Waters Xevo TQD equipped with positive electrospray ionization in the multiple reaction monitoring modes. The clopidogrel was detected at m/z 322.086>212.097 and irbesartan as an internal standard at m/z 429.233>207.131. The sample was prepared with protein precipitation method using acetonitrile, vortex mixed for 10 minutes, and centrifuged at 13,000 rpm for 20 minutes. Results: This method showed a linear result at the concentration range of 0.2-10 ng/ml with râ‰¥0.9997. Conclusions: The developed method provides sensitivity, linearity, precision, and accuracy and is suitable for analysis of clopidogrel in human plasma using LC-MS/MS.